A method for rapid quantitative measurement of interlayer ionic interaction forces in layered electrode materials

By using multi-beam interference fringe technology to measure layer spacing and interaction forces on layered electrode materials, the complex and time-consuming problems of traditional methods are solved, and high-precision and rapid measurement of interlayer ion interaction forces of layered electrode materials is achieved. , improves battery performance and life.

CN114646599BActive Publication Date: 2024-12-13BEIJING INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210275511.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-21
Publication Date
2024-12-13
Estimated Expiration
2042-03-21

AI Technical Summary

Technical Problem

The existing technology is difficult to quickly quantify the ionic interaction forces between layers of layer electrode materials, resulting in mechanical damage to the layered structure and reduced battery life, and traditional methods are complex and time-consuming.

Method used

The layer spacing is measured by mechanical methods through the multi-beam interference fringes formed between transparent material cylindrical surfaces with axes perpendicular to each other, and the interaction force is calculated in combination with the elastic modulus to achieve high spatial resolution layer spacing and interaction force curve measurement.

Benefits of technology

Achieve high-precision, fast and simple measurement of ion interaction force between layers of layer electrode materials, with a spatial accuracy of up to 0.1 Åm, avoiding the complex sample preparation process of traditional electrochemical methods, saving time and cost, and measuring multiple measurements The overall interaction force of interlayer structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114646599B_ABST
    Figure CN114646599B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for rapid quantitative measurement of the interlayer ion interaction force of layered electrode materials, and belongs to the field of energy batteries. The present invention adopts a mechanical method to directly obtain the interlayer ion structure of the layered electrode material, and while mechanically controlling the interlayer distance, uses the multi-beam interference fringes with high spatial resolution formed between two cylindrical surfaces whose axes are perpendicular to each other to measure the change in the interlayer spacing, and combines the spring with a known elastic modulus to calculate its interaction force, and obtains the interlayer spacing-interlayer interaction force curve with high spatial resolution. In addition, the overall interlayer spacing after the superposition of multiple interlayer ion structures-interlayer interaction force curve can also be measured simultaneously. This method avoids the complex process of preparing the interlayer ion structure of layered electrode materials by traditional electrochemical methods, and can simultaneously measure the interlayer spacing and interlayer interaction force of the interlayer ion structure of layered electrode materials, with high precision, simple and direct operation, and high portability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for rapidly and quantitatively measuring the interlayer ion interaction force of layered electrode materials, and belongs to the field of energy batteries. Background Art

[0002] With the continuous development of society, batteries have provided great convenience for people's daily lives and are widely used in portable mobile devices, electric vehicles, electric aircraft, etc. However, with the continuous development of portable devices and the application of high-power devices such as electric vehicles and electric aircraft, higher and higher requirements are placed on the energy density and rate performance of batteries.

[0003] As a classic embedded electrode, layered electrode materials store energy by embedding ions between their layers. During the ion embedding process, the layers of the layered electrode materials are stretched, causing expansion and deformation between the layers of the layered electrode materials, forming an interaction force between the layers. The interaction force caused by the deformation of the embedded ions in the layered electrode materials in turn limits the further embedding of subsequent ions, forming a coupling effect between mechanics and electrochemistry. This coupling effect not only affects the charge and discharge rate of the electrode material, but also causes mechanical damage to the layered electrode, greatly reducing the life of the battery. Therefore, it is urgent to measure the interlayer spacing of the interlayer embedded ion structure of the layered electrode material - the relationship between the interlayer interaction force, so as to eliminate the negative impact of this coupling effect on the battery.

[0004] At present, the technology that can measure the relationship between the interlayer spacing and the interlayer interaction force of the interlayer ion structure of layered electrode materials is AFM. To use AFM for measurement, it is necessary to use complex electrochemical sample preparation methods to prepare the interlayer ion structure, which requires high experimental skills and is time-consuming and labor-intensive. During the measurement, the AFM tip is used to perform local point pressure measurements on the sample. The point measurement method has a slow measurement speed and is difficult to represent the surface-to-surface interaction between layers in the interlayer ion structure. The measurement accuracy of AFM in distance is only 1 angstrom, and it is impossible to capture changes in interlayer spacing at a smaller scale than it. Therefore, it is necessary to develop a method that can quickly and quantitatively measure the interlayer ion interaction force of layered electrode materials. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of mechanical damage to the layered structure caused by the mechanical / electrochemical coupling of the layered electrode material, and to provide a method for rapid quantitative measurement of the interlayer ion interaction force of the layered electrode material; the present invention adopts a mechanical method to directly obtain the interlayer embedded ion structure of the layered electrode material, and while mechanically controlling the interlayer distance, uses the multi-beam interference fringes with high spatial resolution formed between two cylindrical surfaces with axes perpendicular to each other to measure the change in the interlayer spacing, and combines the spring with a known elastic modulus to calculate its interaction force, and obtains a high spatial resolution interlayer spacing-interlayer interaction force curve. In addition, the overall interlayer spacing after the superposition of multiple interlayer embedded ion structures-interlayer interaction force curve can also be measured simultaneously. This method avoids the complex process of preparing the interlayer embedded ion structure of the layered electrode material by the traditional electrochemical method, and can simultaneously measure the interlayer spacing and interlayer interaction force of the interlayer embedded ion structure of the layered electrode material, with high precision, simple and direct operation, and high portability.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] 1. A method for rapid quantitative measurement of interlayer ionic interaction forces of layered electrode materials, characterized in that:

[0008] Step 1: Installing layered electrode material films on the surfaces of transparent cylindrical materials whose axes are perpendicular to each other; arranging a semi-transparent metal layer between the layered electrode material film and the cylinder; adding electrolyte between the two cylindrical surfaces so that the layered electrode material film is always placed in the electrolyte;

[0009] Step 2: Move the two cylinders closer to each other. When the interaction force of the layered electrode material film oscillates, start fine control and record the equal-color fringes at different times. Calculate the absolute distance between the two surfaces by comparing the movement of the interference fringes. Calculate the interaction force between the two surfaces by the change in the absolute distance and the known spring stiffness.

[0010] The absolute distance between two surfaces is calculated as:

[0011]

[0012] n g and n e Respectively represent the refractive index of the layered electrode material film layer and the electrolyte layer, D represents the distance between the two layered electrode material surfaces, and It represents the wavelength of two adjacent fringes when the two surfaces of the layered electrode are in contact. and It represents the wavelength of two adjacent fringes when the thickness of the electrolyte layer between the two surfaces is D, f m≈1.024+1 / m is the correction factor introduced by considering the refractive index dispersion and phase change reflected at the metal mirror interface, and m represents the order of the fringe;

[0013] Interaction force:

[0014] F=k·ΔD

[0015] Where F represents the interaction force, k represents the elastic coefficient of the spring, and ΔD represents the change in the absolute distance between the two surfaces;

[0016] Step 3: Repeat step 2 to obtain multiple sets of corresponding distance and interaction force data, and further obtain the interlayer spacing-interlayer interaction force relationship of the interlayer embedded ion structure of the layered electrode material.

[0017] The electrolyte needs to be kept at a constant temperature during the test;

[0018] The light path is emitted from the light source, passes through the achromatic lens to eliminate the chromatic aberration of the light, is refracted by the reflector, vertically passes through the interference cavity formed by the lower cylindrical surface and the upper cylindrical surface perpendicular to each other, is refracted by a reflector again, passes through the beam splitter to form equal-color fringes, and is received and recorded by the spectrometer;

[0019] The two transparent cylindrical surfaces, including the lower cylindrical surface and the upper cylindrical surface, are composed of a layered electrode material film layer with a metal layer plated on the back side adhered to the surface of a transparent cylindrical support body with glue, so it also includes a glue layer, a silver-plated layer and a layered electrode material film layer.

[0020] Preferably, in order to ensure the passage of the light path, the spring with known stiffness is selected as a spring of a cantilever beam structure.

[0021] Preferably, the electrolyte is a metal ion system electrolyte, and the metal ions include lithium, sodium, potassium, magnesium, etc. Different metal ion system electrolytes are selected according to measurement requirements.

[0022] Preferably, in order to ensure its light transmittance, the cylindrical support body supporting the cylindrical surface of the layered electrode material film is made of transparent materials, including various transparent glasses, transparent resins, such as silicon dioxide, PMMA, PC, PET, etc.

[0023] Preferably, in order to reduce defects of the layered electrode material film layer, the layered electrode material film is a layered electrode material film with few layers.

[0024] Preferably, in order to reduce the influence of the glue layer on the optical path, a glue with a reflectivity close to the reflectivity of the transparent cylindrical support should be selected, so a UV-curing optical glue is selected.

[0025] As a further preference, when preparing the cylindrical lower cylindrical surface and the upper cylindrical surface, in order to ensure the transmission of light by the layered electrode material layer, a layered electrode material film of 3-10 layers is selected. In order to increase the reflection of light by the layered electrode material film without affecting the transmission of light on the surface, so as to form clearer multi-beam interference fringes, a metal film with a thickness of 30-55 nanometers should be plated on the back of the layered electrode material film. Therefore, a 30-nanometer silver film is evaporated on the back of the layered electrode material film to form a silver-plated layer. At the same time, in order to ensure that the surface does not shift during the measurement process, it is necessary to adhere it to the outer surface of the transparent glass support with glue, and the glue is cured to form a glue layer.

[0026] As a further preference, during the measurement process, the light beam is adjusted to pass vertically through the interference cavity formed by the two transparent cylindrical surfaces to form multi-beam interference. After passing through the beam splitter, equal-color gradation stripes are finally formed. By reading the movement of the stripes, the absolute distance between the surfaces of the two layered electrode material layers can be measured. By observing the displacement of the end of the cantilever beam spring with known stiffness, the interaction force between the surfaces of the two layered electrode material layers can be measured. In order to form more accurate multi-beam interference stripes, it should be ensured that the axes of the cylindrical surfaces where the two layered electrode material layers are located remain perpendicular to each other, and their surfaces are completely immersed in the environment of the electrolyte medium layer. The surface of the layered electrode material layer completely immersed in the electrolyte will naturally form a double electric layer. As the distance between the two surfaces continues to approach, the double electric layers on its surface overlap, and a repulsive force is formed between the two surfaces due to the electrostatic action of the double electric layer. As the two surfaces continue to approach, the solvated metal ions in the double electric layer gradually present a multi-layer regular arrangement, and are gradually squeezed out as the surface spacing decreases. At this time, the interaction force between the two surfaces presents an oscillating form. As the two surfaces continue to approach, the number of solvated metal ion layers in the double electrical layer gradually decreases until only the last layer remains. As the surface spacing further decreases, the solvated shell is shed and an independent metal ion layer exists between the two layered electrode material surfaces. At this time, the two layered electrode material layers and the metal ion layer between them form a Figure 3 The layered electrode material embedded ion structure shown in the figure ends the oscillation of the force, and the distance between the two surfaces is about 5 nanometers. Fine spatial stepping is used to further shorten the distance between the two layered electrode material layers until they touch each other, and then the distance between the two layered electrode material layers is increased. At the same time, the distance between the two surfaces and the interaction force are measured and recorded to obtain the interlayer spacing of the layered electrode material embedded ion structure - the curve of the interlayer interaction force.

[0027] As a further preferred embodiment, when it is necessary to measure the macroscopic interaction force of the entire ion-embedded structure of multiple layered electrode materials, the longitudinal length and the number of arrangements of the transparent cylindrical supports in the lower cylindrical surface and the upper cylindrical surface can be extended so that each of them forms a Figure 2The cylindrical surface is shown in rows. At this time, the lower cylindrical surface and the upper cylindrical surface axis are kept vertically arranged, and the surface contact points of the layered electrode material in the form of an array can be obtained by the same method. Then, according to the operation of a single surface contact point, the overall interlayer spacing after the accumulation of multiple layered electrode material embedded ion structures - the curve of the interlayer interaction force can be obtained.

[0028] Beneficial effects:

[0029] 1. The present invention discloses a method for rapidly and quantitatively measuring the interlayer ion interaction force of layered electrode materials. By passing a light beam vertically through the surfaces of two mutually perpendicular transparent layered electrode material films, the spacing between the surface layers of the layered electrode material in the layered electrode material embedded ion structure is measured, and the interaction force between the surface layers can be directly measured with a spatial accuracy of up to 0.1 angstroms. The interlayer spacing and interlayer interaction force information with high spatial accuracy can be obtained simultaneously, and the interlayer spacing-interlayer interaction force curve of the layered electrode material embedded ion structure can be obtained.

[0030] 2. The present invention discloses a method for rapidly and quantitatively measuring the interlayer ionic interaction force of layered electrode materials. By allowing the surfaces of two layered electrode materials immersed in an electrolyte to gradually approach each other, a layered electrode material embedded ion structure is naturally formed eventually. This avoids the complicated sample preparation process of traditional electrochemical methods. The method is simple and easy to operate, greatly saves the time cost of the experiment, and has high portability.

[0031] 3. The present invention discloses a method for rapid quantitative measurement of the interlayer ionic interaction force of layered electrode materials. By expanding the transparent cylindrical support, the overall interlayer spacing-interlayer interaction force curve after the superposition of multiple layered electrode material embedded ion structures can be obtained simultaneously, which is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention discloses a method for rapidly and quantitatively measuring the interlayer ion interaction force of a layered electrode material;

[0033] Figure 2 It is a schematic diagram of the multilayer structure of the upper and lower cylindrical surfaces in a method for rapidly and quantitatively measuring the interlayer ionic interaction force of layered electrode materials disclosed in the present invention.

[0034] Figure 3 It is a schematic diagram of the interlayer of embedded ions between layered electrodes formed when the surfaces of two layered electrodes are very close in a method for quickly and quantitatively measuring the interlayer ionic interaction force of layered electrode materials disclosed by the present invention.

[0035] Among them: 1—light source; 2—achromatic lens; 3—first reflector; 4—lower cylindrical surface; 5—upper cylindrical surface; 6—beam splitter; 7—spectrometer; 8—spring; 9—electrolyte medium layer; 10—transparent cylindrical support; 11—glue layer; 12—metal coating; 13—layered electrode layer; 14—metal ion layer; 15—second reflector. DETAILED DESCRIPTION

[0036] The following will describe a method for rapidly and quantitatively measuring the interlayer ionic interaction force of layered electrode materials proposed by the present invention in conjunction with the embodiments and drawings.

[0037] Embodiment 1:

[0038] This embodiment discloses an experimental process for measuring the interlayer spacing-interlayer interaction force curve of the interlayer ion embedding structure of a single layered electrode material using this experimental method. The experimental process mainly includes: preparing a cylindrical surface, including a lower cylindrical surface 4 and an upper cylindrical surface 5; adjusting and correcting the optical path; adjusting the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 to control the formation of the graphene lithium embedding structure; measuring the interlayer spacing-interlayer interaction force curve in the graphene lithium embedding structure; measuring the overall interlayer spacing-interlayer interaction force curve after multiple graphene lithium embedding structures are superimposed.

[0039] The preparation process of the cylindrical surface is as follows: a 5-layered, highly oriented pyrolytic graphene film is selected, one side is selected as the back side of the few-layer graphene film, a 30-nanometer-thick silver layer is coated on the back side by chemical evaporation, and then it is cut into a size suitable for the cylindrical surface; the graphene film is pasted on the surface of the transparent glass cylinder by ultraviolet curing optical adhesive, and the surface is smoothed, and after it is cured, the lower cylindrical surface 4 and the upper cylindrical surface 5 can be obtained.

[0040] The process of adjusting and correcting the optical path is as follows: fix the lower cylindrical surface 4 and the upper cylindrical surface 5 on a fixture that can adjust the distance between the two so that their axes remain perpendicular to each other; turn on the light source 1, adjust the optical path to remain perpendicular to the axes of the lower cylindrical surface 4 and the upper cylindrical surface 5, so that the optical path passes perpendicularly through the interference cavity formed by the lower cylindrical surface 4 and the upper cylindrical surface 5; adjust the distance so that the lower cylindrical surface 4 and the upper cylindrical surface 5 lightly touch each other, adjust the position where the center of the optical path passes so that the center of the optical path is aligned with the center of the contact surface formed by the lower cylindrical surface 4 and the upper cylindrical surface 5; keep the lower cylindrical surface 4 and the upper cylindrical surface 5 lightly touching each other. state, and use the interference fringes observed at this time to calibrate the optical parameters of each layer in the optical path, including the glass support 10, the glue layer 11, the silver-plated layer 12 and the few-layer graphene layer 13; fill a sufficient amount of lithium ion electrolyte between the lower cylindrical surface 4 and the upper cylindrical surface 5 to ensure that the lower cylindrical surface 4 and the upper cylindrical surface 5 are completely immersed in the lithium ion electrolyte, and further correct the optical parameters of each layer including the glass support 10, the glue layer 11, the silver-plated layer 12, the few-layer graphene layer 13 and the electrolyte medium layer 9; record the fringes position where the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 is zero as the reference position.

[0041] The process of controlling the formation of graphene lithium embedded structure and measuring its interlayer spacing-interlayer interaction force curve is as follows: after adjusting the optical path, adjust the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 to make them completely separated until the interaction force is zero; slowly adjust the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 to make them close to each other, and observe their interaction force; after the interaction force successively presents as repulsive force and oscillating force, the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 is about 5 nanometers, and stop adjusting the spacing; use fine distance control steps to control the lower cylindrical surface 4 and the upper cylindrical surface 5 to make them slowly approach, and record the spacing and interaction force between the lower cylindrical surface 4 and the upper cylindrical surface 5 every time the distance is changed, until the spacing reaches zero; continue to use fine distance control steps to control the lower cylindrical surface 4 and the upper cylindrical surface 5 to make them slowly move away, and record the spacing and interaction force between the lower cylindrical surface 4 and the upper cylindrical surface 5 every time the distance is changed, until the interaction force presents an oscillating form; by making one-to-one correspondence between the interlayer spacing and the interlayer interaction force, the interlayer spacing-interlayer interaction force curve can be obtained.

[0042] Embodiment 2:

[0043] This embodiment discloses a simple verification process of the experimental formula. According to the interference principle, the relationship between the wavelength of multi-layer interference and the distance between the layers can be obtained as follows:

[0044] Where n g and n eRespectively represent the refractive index of the layered electrode material film layer and the electrolyte layer, D represents the distance between the two layered electrode material surfaces, and It represents the wavelength of two adjacent fringes when the two surfaces of the layered electrode are in contact. and It indicates the wavelength of two adjacent fringes when the thickness of the electrolyte layer between the two surfaces is D ± in the fringing order When it is an odd number, it is +. When it is an even number, it is -. When m is an odd number, using a low-order Taylor expansion, we can get:

[0045]

[0046] After simplification, we can get:

[0047]

[0048] Similarly, when m is an even number, using Taylor expansion we can get:

[0049]

[0050] After simplification, we can get:

[0051]

[0052] Considering the refractive index dispersion and phase change reflected at the metal mirror interface in actual situations, a correction factor is introduced:

[0053] f m ≈1.024+1 / m

[0054] In summary, the distance calculation formula is as follows:

[0055]

[0056] When measuring the interaction force F, according to Hooke's law, the relationship between the interaction force and the change in the distance between the two surfaces ΔD can be obtained as follows:

[0057] F=k·ΔD

[0058] Where k is the elastic constant of the spring.

[0059] Embodiment 3:

[0060] This embodiment discloses an experimental process for measuring the interlayer spacing-interlayer interaction force curve of multiple layered electrode material interlayer ion embedding structures using this experimental method. The experimental process mainly includes: preparing a cylindrical surface, including a lower cylindrical surface 4 and an upper cylindrical surface 5; adjusting and correcting the optical path; adjusting the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 to control the formation of the graphene lithium embedding structure; measuring the interlayer spacing-interlayer interaction force curve in the graphene lithium embedding structure; measuring the overall interlayer spacing-interlayer interaction force curve after multiple graphene lithium embedding structures are superimposed.

[0061] The preparation process of the cylindrical surface is as follows: select a 5-layer few-layer highly oriented pyrolytic graphene film, select one side as the back of the few-layer graphene film, coat a layer of silver with a thickness of 30 nanometers on the back by chemical evaporation, and then cut it into a size suitable for the cylindrical surface; prepare multiple groups of silver-plated graphene materials according to the same method; use upper and lower cylindrical pairs that can form multiple contact points after expansion; use ultraviolet curing optical adhesive to sequentially stick the prepared multiple groups of graphene films on the contact point positions of the transparent glass cylindrical surface after expansion, and smooth the surface, and wait for it to solidify to obtain multiple groups of lower cylindrical surfaces 4 and upper cylindrical surfaces 5 after expansion.

[0062] The process of adjusting and correcting the optical path is as follows: fix the lower cylindrical surface 4 and the upper cylindrical surface 5 on a fixture that can adjust the distance between the two so that their axes remain perpendicular to each other; turn on the light source 1, adjust each optical path to remain perpendicular to the axes of the lower cylindrical surface 4 and the upper cylindrical surface 5, so that the optical path passes perpendicularly through the interference cavity formed by the lower cylindrical surface 4 and the upper cylindrical surface 5; adjust the distance so that the lower cylindrical surface 4 and the upper cylindrical surface 5 lightly contact each other, adjust the position where the center of the optical path passes so that the center of the optical path is aligned with the center of the contact surface formed by the lower cylindrical surface 4 and the upper cylindrical surface 5; keep each contact point of the lower cylindrical surface 4 and the upper cylindrical surface 5 lightly relative to each other The optical parameters of each layer in the optical path are calibrated using the interference fringes observed at this time, including the glass support 10, the glue layer 11, the silver-plated layer 12 and the few-layer graphene layer 13; a sufficient amount of lithium-ion electrolyte is filled between the lower cylindrical surface 4 and the upper cylindrical surface 5 to ensure that the lower cylindrical surface 4 and the upper cylindrical surface 5 are completely immersed in the lithium-ion electrolyte, and the optical parameters of each layer including the glass support 10, the glue layer 11, the silver-plated layer 12, the few-layer graphene layer 13 and the electrolyte medium layer 9 are further corrected; the position of the fringes with zero spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 is recorded as a reference position.

[0063] The process of controlling the formation of graphene lithium embedded structure and measuring its interlayer spacing - interlayer interaction force curve is as follows: after adjusting the optical path, adjust the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 to make them completely separated until the interaction force is zero; slowly adjust the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 to make them close to each other, and observe their interaction force; after the interaction force successively presents as repulsive force and oscillating force, the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5 is about 5 nanometers, and stop adjusting the spacing; use fine distance control step to control the spacing between the lower cylindrical surface 4 and the upper cylindrical surface 5. The cylindrical surface 5 is used to slowly approach them, and the spacing and interaction force between the lower cylindrical surface 4 and the upper cylindrical surface 5 are recorded each time the distance changes until the spacing reaches zero; the lower cylindrical surface 4 and the upper cylindrical surface 5 are continued to be controlled with fine distance control steps to slowly move them away, and the spacing and interaction force between the lower cylindrical surface 4 and the upper cylindrical surface 5 are recorded each time the distance changes until the interaction force exhibits an oscillating form; the interlayer spacing and the interlayer interaction force are matched one by one, and the interlayer spacing-interlayer interaction force curve after the superposition of multiple layered embedded ion structures can be obtained.

[0064] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for rapid quantitative measurement of interlayer ionic interaction forces of layered electrode materials, characterized in that: Step 1: Installing layered electrode material films on the surfaces of transparent cylindrical materials whose axes are perpendicular to each other; arranging a semi-transparent metal layer between the layered electrode material film and the cylinder; adding electrolyte between the two cylindrical surfaces so that the layered electrode material film is always placed in the electrolyte; Step 2: Move the two cylinders closer to each other. When the interaction force of the layered electrode material film oscillates, start fine control and record the equal-color fringes at different times. Calculate the absolute distance between the two surfaces by comparing the movement of the interference fringes. Calculate the interaction force between the two surfaces by the change in the absolute distance and the known spring stiffness. The absolute distance between two surfaces is calculated as: n g and n e Respectively represent the refractive index of the layered electrode material film layer and the electrolyte layer, D represents the distance between the two layered electrode material surfaces, and It represents the wavelength of two adjacent fringes when the two surfaces of the layered electrode are in contact. and It represents the wavelength of two adjacent fringes when the thickness of the electrolyte layer between the two surfaces is D, f m ≈1.024+1 / m is the correction factor introduced by considering the refractive index dispersion and phase change reflected at the metal mirror interface, and m represents the order of the fringe; Interaction force: F=k·ΔD Where E represents the interaction force, k represents the elastic coefficient of the spring, and ΔD represents the change in the absolute distance between the two surfaces; Step 3: Repeat step 2 to obtain multiple sets of corresponding distance and interaction force data, and further obtain the interlayer spacing-interlayer interaction force relationship of the interlayer embedded ion structure of the layered electrode material.

2. The method for rapid quantitative measurement of interlayer ionic interaction forces of layered electrode materials according to claim 1, characterized in that: When there are multiple groups of mutually perpendicular transparent material cylinders, multiple interlayer ion embedding structures of layered electrode materials can be obtained, and the overall interlayer spacing and interlayer interaction force curves after the multiple interlayer ion embedding structures of layered electrode materials are superimposed can be measured simultaneously.

3. The method for rapid quantitative measurement of interlayer ionic interaction forces of layered electrode materials according to claim 1, characterized in that: The mutually perpendicular transparent material cylinders form a circular opposite surface of micro-nano scale at the contact position.

4. The method for rapid quantitative measurement of interlayer ionic interaction forces of layered electrode materials according to claim 1, characterized in that: The spring is a cantilever beam spring.

5. The method for rapid quantitative measurement of interlayer ionic interaction forces of layered electrode materials according to claim 1, characterized in that: The electrolyte is a metal ion system electrolyte.

6. The method for rapid quantitative measurement of interlayer ionic interaction forces of layered electrode materials according to claim 1, characterized in that: The thickness of the metal layer is in the range of 30-55 nanometers.

7. A device for implementing the method according to any one of claims 1 to 6, characterized in that: The invention comprises a light source (1), an achromatic lens (2), and a spectrometer (7); light emitted by the light source (1) passes through the achromatic lens (2) to eliminate chromatic aberration, is refracted by a first reflector (3), and then passes through an interference cavity formed by a lower cylindrical surface (4) and an upper cylindrical surface (5) perpendicular to each other, is refracted by a second reflector (15), passes through a beam splitter (6), and forms equal-color stripes, which are received and recorded by the spectrometer (7).

Citation Information

Patent Citations

  • Method for improving ion intercalation / deintercalation rate in energy storage layered material

    CN112666242A

  • Vertical-resonator surface-emission laser

    JP2012129245A

  • Method of Estimating Surface Ion Density

    US20100072955A1

  • Systems and methods for determining characteristics of semiconductor devices

    US20200088784A1